Experimental investigation of thermo-physical properties, convective heat transfer and pressure drop of functionalized graphene nanoplatelets aqueous nanofluid in a square heated pipe. (15th April 2016) - Yarmand, Hooman; Gharehkhani, Samira; Shirazi, Seyed Farid Seyed; Amiri, Ahmad; Alehashem, Maryam Sadat; Dahari, Mahidzal; Kazi, S.N.
Graphical abstract: Schematic of functionalization process and making of nanofluid. Highlights: Stable dispersion of GNP nanofluids are prepared with the functionalization method. Remarkable thermal conductivity enhancement was observed for all nanofluid samples. Overall heat transfer coefficient of nanofluids have been significantly enhanced. Enhancement of friction factor as a negative parameter is negligible. Abstract: In the present study, a facile method is used for preparation of functionalized graphene nanoplatelets (f-GNP) nanofluids. The effective thermal conductivity, density, viscosity, specific heat capacity, overall heat transfer coefficient and friction factor for fully developed turbulent flow of f-GNP/water nanofluids flowing through a square pipe at a constant heat flux were studied. f-GNP uniform nanocomposite was produced from a simple acid treatment reaction procedure. The surface characterization was performed by various techniques such as XRD, FESEM, FTIR and Raman. The f-GNP nanofluids were prepared by dispersing the functionalized nanoparticles in base fluid (water) without the assistance of a surfactant. As made nanofluids were stable for a long time and no sedimentation was observed. The experimental data for f-GNP nanofluids have shown significant enhancement in thermal conductivity and overall heat transfer coefficient in comparison to the corresponding water data. The percentage of enhancement is a function of weight concentration of nanoparticles and temperature. Highest improvement of overall heat transfer coefficient is 19.68% with 9.22% raise in friction factor for the weight concentration of 0.1% at a Reynolds number of 17, 500 compared to those data from the base fluid.